2019
DOI: 10.3390/biomedicines7040098
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry, Pharmacology and Therapeutic Potential of the Edible Mushroom Dictyophora indusiata (Vent ex. Pers.) Fischer (Synn. Phallus indusiatus)

Abstract: Dictyophora indusiata (Vent. Ex. Pers.) Fischer or Phallus indusiatus is an edible member of the higher mushroom phylum of Basidiomycetes. Known for its morphological elegance that gave it the names bridal veil fungus, veiled lady or queen of the mushrooms, it has numerous medicinal values that are beginning to be acknowledged through pharmacological efficacy studies. In an attempt to promote research on this valuable natural resource, the present communication aims to provide a comprehensive review of the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 78 publications
(144 reference statements)
0
24
0
Order By: Relevance
“…D. indusiata , a saprophytic fungus of bamboo forest, has been one of the most popular edible mushrooms for its edible values and medicinal functions ( Habtemariam, 2019 ). Wang Y. L. et al (2019) extracted a purified polysaccharide DIP ( Figure 3E ) from D. indusiata , and investigated the anti-colitis effect and underlying mechanism of DIP in DSS-treated mice.…”
Section: Polysaccharides From Mushroomsmentioning
confidence: 99%
“…D. indusiata , a saprophytic fungus of bamboo forest, has been one of the most popular edible mushrooms for its edible values and medicinal functions ( Habtemariam, 2019 ). Wang Y. L. et al (2019) extracted a purified polysaccharide DIP ( Figure 3E ) from D. indusiata , and investigated the anti-colitis effect and underlying mechanism of DIP in DSS-treated mice.…”
Section: Polysaccharides From Mushroomsmentioning
confidence: 99%
“…People who incorporate mushrooms into their diets, even in small amounts (more than twice a week), seem to have a lower risk of mild cognitive impairment, usually preceding Alzheimer's disease [196]. Mushrooms contain many other substances whose exact role in brain health is not yet clear, but they include hericenones, erinacines terpenoids, scabronines, isoindolinones, sterols, and dictyophorines, which are a series of compounds that could contribute to the growth of nerve and brain cells [197].…”
Section: Mushrooms and Neurological Disordersmentioning
confidence: 99%
“…In recent years, studies have shown that polysaccharide from Craterellus cornucopioide and Dictyophora indusiata (Vent.ex Pers) Fisch have some interesting biological activities, such as bacteriostasis, antioxidation etc. (Yang et al, 2018;Guo et al, 2019;Habtemariam, 2019). However, there are some differences in the structure of polysaccharides from different regions, and there is no report on the study of the polysaccharides of Craterellus cornucopioide and Dictyophora indusiata (Vent.ex Pers) Fisch from Qingjiang county of Sichuan Province.…”
Section: Introductionmentioning
confidence: 99%